The Role of Health on Economic Development. - Jallow, Assan (International Journal of Health Statistics, 2020)
In this project the main aim is to investigate the role of health on economic development. In doing so my inspiration was derive for the augmented neoclassical theoretical firm work base on the hypothesis that health has a positive impact on economic growth, looking at specification 1 and 4 are basic linear regression model which are used to capture the liner relationship between health and economic development. And looking at the graphs from our “appendix” we will observe a strong positive correlation between the variables. We also used life expectancy as a proxy for health which was positive and significant across all specification, which affirms that’s health have a positive and significant impact on economic growth as well as output per capita. For specification 3 and 6, we ran a “flexmix” which gives a reflection of a conclusion that our data most not be “cluster”, this is also supported by the pair wise plot which actually shows no meaningful cluster at a visual inspection.
Keywords: Health; Economic Growth and flexmix regression